2022
DOI: 10.1159/000523896
|View full text |Cite
|
Sign up to set email alerts
|

Human Immature Dental Pulp Stem Cells Did Not Graft into a Preexisting Human Lung Adenocarcinoma

Abstract: Mesenchymal stem cell (MSC)-based therapies have been considered an attractive approach for treating Huntington’s disease (HD). However, due to the pulmonary first-passage effect associated with intravenous infusion (the most commonly used route of MSC administration), there is a rising concern that the cells could be entrapped in the lungs and grafted (homing) into preexisting lung cancer. Herein, we report the case of a patient with HD enrolled in a cell therapy phase I clinical trial for HD treatment having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…Using reduction dimension analysis (PCA or principal component analysis), we demonstrated no evidence of the hIDPSCs within the lung adenocarcinoma. This result suggests that transplanted manufactured hIDP-SCs neither home nor graft within the pulmonary nodule [104], reinforcing that the cell therapy with the NestaCell ® is safe even for patients with preexisting lung cancer.…”
Section: Nestacell® Do Not Engraft In Preexisting Malignant Neoplasmmentioning
confidence: 88%
“…Using reduction dimension analysis (PCA or principal component analysis), we demonstrated no evidence of the hIDPSCs within the lung adenocarcinoma. This result suggests that transplanted manufactured hIDP-SCs neither home nor graft within the pulmonary nodule [104], reinforcing that the cell therapy with the NestaCell ® is safe even for patients with preexisting lung cancer.…”
Section: Nestacell® Do Not Engraft In Preexisting Malignant Neoplasmmentioning
confidence: 88%
“…Healing of the periapical tissue and the formation of functional pulp tissue [252] Intrabony lesions Autologous PDLSCs Surgery, implantation in the affected sites Reduction in probing depth [253] Cleft lip and palate Autologous SHED Surgery, implantation in a hydroxyapatite-collagen sponge Generation of bone tissue [254] Erectile dysfunction CMs SHED Injections into the corpora cavernosa of the penis Improvement of erections [255] Diabetes mellitus 2 Allogeneic SHED Intravenous Decreased glycosylated hemoglobin and glycosylated serum albumin levels and caused fever, fatigue, and rash [256] Huntington's disease associated with primary lung adenocarcinoma Allogeneic SHED Intravenous Cells did not graft (homing) in the pre-existing tumor [257] Irreversible pulpitis Autologous DPSCs…”
Section: Apical Lesions Autologous Shed Administration In Root Canalsmentioning
confidence: 99%
“…In this study, the international index of erectile function (IIEF-5), which is clinically used to screen for erectile function and to assess treatment efficacy, was increased after SHED-CM injection into the corpus cavernosum of erectile dysfunction patients[ 64 ]. A case report indicated that SHED intravenous administrations could decrease the scale of unified Huntington’s disease rating, which is designed to assess clinical performance and capacity in patients with Huntington’s disease[ 65 , 66 ]. Meanwhile, the patient with Huntington’s disease also suffered from preexisting pulmonary nodules, and SHED injection did not result in long-term tropism or homing for the patient’s lung adenocarcinoma[ 65 ].…”
Section: Dsc-based Clinical Trials From Published Articlesmentioning
confidence: 99%
“…A case report indicated that SHED intravenous administrations could decrease the scale of unified Huntington’s disease rating, which is designed to assess clinical performance and capacity in patients with Huntington’s disease[ 65 , 66 ]. Meanwhile, the patient with Huntington’s disease also suffered from preexisting pulmonary nodules, and SHED injection did not result in long-term tropism or homing for the patient’s lung adenocarcinoma[ 65 ]. In a case report by Wang et al [ 30 ], GMSCs were used to treat plaque psoriasis via bolus injection, and they observed fully cleared psoriatic lesions without recurrence.…”
Section: Dsc-based Clinical Trials From Published Articlesmentioning
confidence: 99%